Syllidae (Annelida) from East Timor and the Philippines (Pacific Ocean), with the description of three new species of Syllis Savigny in Lamarck, 1818 - Martínez, María José; Martín, Guillermo San (Zootaxa, 2020)
East Timor is an island located to the south of the Indonesian Archipelago and to the north of Australia, between the Indian and Pacific Oceans. It is included in the Coral Triangle and houses an amazing quantity of marine biodiversity. However, only two species of Syllidae (Annelida) have been reported up to now: Trypanosyllis migueli and T. devae. Based on a small collection from the Australian Museum, we have identified nine genera and 17 species: Brevicirrosyllis mariae, Opisthodonta morena, Sphaerosyllis densopapillata, Branchiosyllis australis, B. exilis, B. maculata, B. verruculosa, Haplosyllis djiboutiensis, Opisthosyllis brunnea, Syllis alternata, S. broomensis, S. corallicola, S. erikae, S. gerlachi, S. hyalina, S. setoensis and Trypanosyllis luzonensis. This is the first record of S. gerlachi outside the Indian Ocean, and B. mariae, O. morena, S. densopapillata, H. djiboutiensis, S. corallicola and S. erikae have not been previously reported in tropical Asia. A specimen of Parahaplosyllis sp. could not be identified due to its poor condition. Three species belonging to Syllis are herein described as new: S. cambuk n. sp. has a large size body, with anterior segments much wider and shorter than posterior ones, long whip-shaped dorsal cirri and bidentate midbody and posterior chaetae, with both teeth equal in size and shape; Syllis hampirmenyatu n. sp. has three chaetae per posterior parapodium, with short and wide blades appearing to be fused with shafts, but still clearly distinguishable from each other, bidentate, with proximal tooth clearly smaller and thinner than distal one; and S. maganda n. sp. is easily recognizable because of its spectacular orange and blue colouration, only observable in living specimens, with broad transverse red stripes on the dorsum forming a distinctive pattern and red spots on the cirri and prostomium observable in both living and fixed specimens. Additionally, Philippine samples from the Museo Nacional de Ciencias Naturales of Madrid have been examined corresponding to S. maganda n. sp. A Philippine specimen of S. maganda n. sp. had a small unidentified specimen of Haplosyllis attached to a posterior dorsal cirrus, which is the first documented case of such an interaction between two species of Syllidae. This provisionally called Haplosyllis sp. is characterized by its simple chaetae with short spur and two very long, distinct curved teeth, very close to each other. A regenerated prostomium and a stolon were also found in other Philippine specimens of S. maganda n. sp.